Emotion, Disclosure, &Amp; Health. 1995
DOI: 10.1037/10182-009
|View full text |Cite
|
Sign up to set email alerts
|

Confrontation: Inhibition, alexithymia, and health.

Abstract: his chapter presents our team's research into alexithymia, emotional T coping, and health. First of all, we will briefly review the literature on the positive effect of confrontation on physical and mental health. We will then set out the basic elements of the alexithymia concept and scale (inability to identify and express emotions). The data on factorial, concurrent, and content validity of the Spanish version of Taylor et al. 's (1988) alexithymia scale will be presented. Next, we will also present data t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
10
0
2

Year Published

1999
1999
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 26 publications
4
10
0
2
Order By: Relevance
“…We found that individuals who are not attentive to their emotions had better outcomes, specifically lower NA and anhedonic depression, if they engaged in the emotional approach interventions. This finding is consistent with past research indicating that people with deficits in emotional processing style will gain greater benefits from expressing their emotions to others or writing about their emotions than others who are more attentive or clear about their emotions (Baker & Berenbaum, 2007;Paez et al, 1995;Salovey et al, 1999;Smyth, 1998).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We found that individuals who are not attentive to their emotions had better outcomes, specifically lower NA and anhedonic depression, if they engaged in the emotional approach interventions. This finding is consistent with past research indicating that people with deficits in emotional processing style will gain greater benefits from expressing their emotions to others or writing about their emotions than others who are more attentive or clear about their emotions (Baker & Berenbaum, 2007;Paez et al, 1995;Salovey et al, 1999;Smyth, 1998).…”
Section: Discussionsupporting
confidence: 92%
“…We hypothesized that individual differences in emotional processing style (i.e., attention to and clarity of emotion) may moderate the effectiveness of emotional approach and problem-focused coping interventions. These hypotheses are consistent with the results of past research suggesting that individuals who lack mood awareness and are less emotionally open benefit more from expressive writing and other mechanisms to express their emotions than do people who are more attentive and clear about their emotions (Baker & Berenbaum, 2007;Lumley, 2004;Paez, Basabe, Valdoseda, Velasco, & Iraurgi, 1995;Paez, Velasco, & Gonzalez, 1999;Salovey et al, 1999).…”
Section: Introductionsupporting
confidence: 88%
“…Therefore, it is plausible that ''forcing'' an individual low in attention to identify their emotions, and the source of their emotions, was useful because their emotions provided guidance to eventually solve the problem (Greenberg 2002;Paez et al 1995). Consistent with our past research we found that individuals high in attention to their emotions had better outcomes if assigned to the PFC intervention, but only if one's partner was unsupportive.…”
Section: Discussionsupporting
confidence: 87%
“…Sifneos (1973;1996) argued that alexithymia is the most prominent characteristic of people with psychosomatic complaints. Alexithymia refers to a limited ability to identify and communicate one's own emotions (Bagby & Taylor, 1999;Paez, Basabe, Valdoseda, & Iraurgi, 1995;Sifneos, 1973;1996;Taylor, Bagby, & Parker, 1991). It is argued that every emotion consists of more or less notable physical reactions, such as sweating, a faster heart beat, and tension in the abdominal area.…”
Section: Introductionmentioning
confidence: 99%